Do SMEs halal food products measure up to customer expectation? : an empirical investigation - Abdul Salam, Siti Soleha; Othman, Mohhidin; Ungku Zainal Abidin, Ungku Fatimah; Kamarulzaman, N. A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
In order to increase and maintain their competitiveness and profitability, manufacturers of Halal food products from small and medium-sized enterprises (SMEs) need to continuously improve their products. Thus, in order to identify the aspects of the products that need improvement and to meet the changing expectation of Muslim consumer, manufacturers should constantly monitor their consumer satisfaction. This study reports an application of the expectancy-disconfirmation theory (EDT) in examining the gap (disconfirmation) between customer expectation and perceived performance on SMEs halal food products. Halal confectionery products produced by SMEs were chosen as the focus of the study. A total of 403 usable questionnaires consisted of 45 determinants measuring expectation and perceived performance were collected from Muslim consumers within the Klang Valley area. The results of the analysis indicate that all attributes experienced negative disconfirmation which points toward the conclusion that in overall SMEs Halal food products unable to measure up to customer expectation. Specially, in term of features related to safety, labelling and marketing of the products. Findings of this study reaffirm the manufacturers need to continuously examine their business strategies in tandem with the increasing demands of halal food products and also to accommodate the shift in the preferences and standard in halal food selection among Muslim consumer.